Montagem, anotação e análises comparativas dos genomas mitocondriais de animais representantes das raças bovinas: Gir e Guzerá e o desafio da montagem de novo do genoma nuclear dessas duas raças usando sequenciamento de nova geração - Juliana Assis Geraldo (2015)
This study aimed at assembling the mitochondrial genome (mtDNA) of two Asian cattle breeds (Bos indicus), Guzerá and Gir. Both of these breeds are the main milk production in Brazil. We assembled the mtDNA of both breeds to improve the understanding of the mtDNA molecular diversity within the Bos genus. Comparative analysis with other cattle genomes was performed and we found two of the genomes assembled, carry the mtDNA of taurine origin and two the zebu origin. Changes in cellular functions from the variations between mtDNAs were not found. Through phylogenetic reconstruction was possible to classify the animals Gir 1 and 3 in Guzerá haplogroup I2, and the Indian subcontinent as probable point of origin of domestication of animals. The Gir 2 individual was classified as haplogroup T3 having its domestication originated in the Near East and the individual Guzerá 4 was classified as haplogroup T1c "Africa-derived-American." The statistical support values of the trees generated with the complete mitochondrial sequence were more robust compared to other trees generated (hypervariable region D-loop and all the genes encoding proteins concatenated). The complete mitochondrial sequences will be deposited in public databases to contribute to future work of bovine genetics. Furthermore, in this study we also work with the pilot project for assembly a nuclear genome from six animals (three Gir and three Guzerá). For this strategy was used a Next Generation Sequencing of four different platforms (SOLiD, Miseq, PacBio and Hiseq). The HiSeq platform was the most suitable for working with complex genomes such as cattle. This study provides a model of experimental design and idealization of data that could be used in future projects, and also point out the direction to complete the new genome assembly to Gir and Guzerá breeds.